The Blade of AI: The Double-Edged Impact of AI on Employee Performance: A Systematic Literature Review - Rian Oktafiani; Nur Wening; Reinardus Dwi Prio C; Agung Hartadi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2026)
Although the use of artificial intelligence (AI) in businesses has a complicated effect on worker performance, there are drawbacks as well, like technostress and concerns about AI replacing human labor. This study uses a systematic literature analysis of 14 publications that were acquired from the Scopus database in accordance with PRISMA criteria to determine the factors that affect the effect of AI on employee performance. Results indicate that while technostress and technology anxiety have a detrimental impact, factors like skill development, supportive leadership, and successful AI adoption have a favorable influence. This study offers fresh perspectives on managing the effects of AI in a balanced manner. Future research should investigate how psychological aspects interact with AI and examine moderating variables to improve more successful AI implementation tactics in various organizational environments.